SAS 2021 - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden - SAS 2021 - Meteorological, Oceanographic and Ship Data Collected on Icebreaker Oden - Ship-Based Research Support, Swedish Polar Research Secretariat (Swedish Polar Research Secretariat, 2022)
The Synoptic Arctic Survey 2021 was a research expedition on board the Swedish icebreaker Oden to the High Arctic. The data presented here are the meteorological, oceanographical and ship data collected onboard Oden during the expedition.

This data set contains meteorological, oceanographical and ship data collected onboard IB Oden during the expedition Synoptic Arctic Survey 2021, which was an international research cruise to the Arctic Ocean.

Meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure, Cloud height/cloudiness, Photosynthetic Active Radiation (PAR).

Oceanographical variables: Sea water temperature, Conductivity, Salinity and Sound velocity.

Ship data: Position, Speed, Course, Heading, Water depth.

A "Parameter list" which describes the dataset is attached.

Quality Information: No quality check or other processing of the data has been undertaken. Users should be aware of this in further data handling and analysis.

Sommaren 2021 genomfördes forskningsexpeditionen Synoptic Arctic Survey med isbrytaren Oden till Högarktis. De data som presenteras här är meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på Oden under expeditionen.

Data innehåller meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på isbrytaren Oden under forskningsexpeditionen Synoptic Arctic Survey 2021.

Meteorologiska variabler: Lufttemperatur, luftfuktighet, vindriktning/-hastighet, lufttryck, molnhöjd/molnighet, fotosyntetiskt aktiv strålning (PAR).

Oceanografiska variabler: Havsvattentemperatur, konduktivitet, salthalt, ljudhastighet.

Skeppsdata: Position, fart, kurs, stävad kurs, vattendjup.

Se bifogad parameterlista för beskrivning av insamlad data.

Data har inte genomgått kvalitetsgranskning. Användare behöver ta hänsyn till det i all hantering och vidare analys.
SAS 2021 - Meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på isbrytaren Oden - SAS 2021 - Meteorologiska och oceanografiska data, samt skeppsdata, insamlade på isbrytaren Oden
Keywords: SCIENCE KEYWORDS; ATMOSPHERE; ATMOSPHERIC WINDS; WIND SPEED; WIND DIRECTION; VISIBILITY; WEATHER EVENTS; ATMOSPHERIC TEMPERATURE; AIR TEMPERATURE; PRECIPITATION AMOUNT; PRECIPITATION RATE; HUMIDITY; CLOUD FREQUENCY; CLOUD BASE HEIGHT; ATMOSPHERIC PRESSURE; SEA LEVEL PRESSURE; ATMOSPHERIC PRESSURE MEASUREMENTS; SALINITY/DENSITY; SALINITY; CONDUCTIVITY; PHOTOSYNTHETICALLY ACTIVE RADIATION; WATER TEMPERATURE; WATER DEPTH; Atmospheric conditions; Atmosfäriska förhållanden; Coordinate reference systems; Referenskoordinatsystem; Hydrography; Hydrografi; Meteorological geographical features; Geografiska meteorologiska förhållanden; Oceanographic geographical features; Geografiska oceanografiska förhållanden; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Geoscientific Information; Geovetenskap; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Oceans; Kust och hav; Location; Positionering